PROFIL KEBUGARAN JASMANI ANAK USIA 07 s/d 13 TAHUN SEBAGAI SASARAN EVALUASI PENJASORKES - MADE SR UNDY MAHARDKA, I (Pendidikan Dasar, 2009)
Abstrack: The purpose of this research is to describe the level of physical fitness of Indonesian children at the age of 07 to 13 years old. This research used quantitative approach by descriptive method. The subject in this research was gained from 31 provinces by sampling approach. The result of finding in this research are: 1) The purposes of educating the Physical education, sport, and health (Penjasorkes) has not become the objectives of teacher’s evaluation optimally, the objective of evaluation more tend to the result of study by the shape of sport skill and sport performance, 2) the average of children body weight is 33 kilograms, 3) the average of body height  is 136.4 centimetres, 4) the average of VO2Max was founded as much 29 ml/BW.Kg/min, included in the lack fitness category. In more complete sense, it found that the children who have category of very good physical fitness is 1%, good category is 3%, average category is 11%, lack category is 24% and very lack category is 61%. Thus, the physical fitness as the evaluation objectives and the standard of competence in the subjects (SK-MP) Penjasorkes appropriate to the Permendiknas No. 23 of 2006 has not been achieved.